The Influence of Perceived Organizational Support on Employee Performance Mediated by Work-Life Balance at The Balcone Suites & Resort Bukittinggi - Azkarni Kamal; Azmen Kahar (Pt. Threeple Herphi Educate, 2025)
Employee performance is a critical factor in achieving organizational success, particularly in the hospitality industry where service quality is paramount. This study investigates the effect of perceived organizational support (POS) on employee performance, with work-life balance (WLB) as a mediating variable, at The Balcone Suites & Resort Bukittinggi. Employing a quantitative, causal-associative design, data were collected from 94 employees using structured Likert-scale questionnaires. Analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS 4.0. The findings indicate that while POS has a positive but statistically insignificant direct effect on employee performance (β = 0.168, t = 1.739, p = 0.082), it significantly influences work-life balance (β = 0.685, t = 11.832, p < 0.001). Furthermore, WLB has a significant positive effect on employee performance (β = 0.548, t = 5.446, p < 0.001) and mediates the relationship between POS and performance (β = 0.375, t = 4.725, p < 0.001). The R² values suggest that POS explains 46.9% of the variance in WLB, and together with WLB explains 45.5% of the variance in employee performance. These results highlight the pivotal role of work-life balance as a mediating mechanism in enhancing employee outcomes through organizational support. Practical implications emphasize the need for hotel management to foster supportive environments and improve work-life balance initiatives to optimize employee performance.